OPTIMIZING MANAGEMENT AND SERVICE QUALITY IN IMPROVING MEMBER SATISFACTION: A CASE STUDY ON THE ITB AHMAD DAHLAN STUDENT COOPERATIVE - Zulkifli, Muhamad; Wirawan, Aldy (Universitas Muhammadiyah Tangerang, 2025)
Student cooperatives play a vital role in fostering economic empowerment and entrepreneurial development within higher education institutions. However, challenges such as high management turnover, low member participation, and suboptimal service management often hinder their ability to achieve member satisfaction. This study aims to analyze the influence of service management and service quality on member satisfaction in the Student Cooperative of ITB Ahmad Dahlan. Using a quantitative approach, data were collected through questionnaires distributed to active members, and the relationships among variables were examined using structural modeling analysis. The findings reveal that both service management and service quality have a positive effect on member satisfaction. The urgency of this research lies in the need to strengthen the managerial and service functions of student cooperatives to remain adaptive and relevant in the digital transformation era. The study contributes practically by providing recommendations for improving service governance and quality, and theoretically by enriching literature on service management within educational cooperatives. The novelty of this study lies in its integrative approach, combining managerial and service quality dimensions to explain member satisfaction, specifically in the context of student-based cooperative organizations.